Body position influence on cerebrospinal fluid volume redistribution inside the cranial and spinal CSF compartments - Strbačko, I.; Radoš, M.; Jurjević, I.; Orešković, D.; Klarica, M. (Frontiers in Human Neuroscience, 2025)
IntroductionIt is generally accepted that during body position changes from horizontal to vertical there is a short-lasting shift of a certain CSF volume from the cranium into the hydrostatically lower parts of the spinal space, which leads to transitory CSF pressure decrease to negative values.MethodsIn order to test this, we performed MRI volumetry of cranial and spinal part of the CSF space in healthy volunteers of both genders (n = 22) in three different body positions [horizontal (H); elevated head and upper body (H-UP) under an angle about 30° from the base; elevated lower body (B-UP) under an angle about 30° from the base].ResultsVolumes of brain and spinal cord tissue did not change during body position changes. Significant CSF volume (ml) changes occur inside the spinal space in the tested body positions, primarily in the lumbosacral segment (H-UP – 38.1 ± 7.0; H – 34.4 ± 6.5; B-UP – 28.7 ± 6.5), while at the same time no significant CSF volume changes have been observed inside the cranium in two tested positions (H and B-UP) in which it was possible to measure intracranial CSF volume changes or if we sum up cervical and cranial CSF volumes in those positions.ConclusionObserved results suggest that during the changes of body position CSF volume redistribution occurs, primarily inside the spinal and not the cranial space. This is in accordance with the new hypothesis by which spinal intradural space can significantly change its volume due to its elasticity, thus adjusting to the influence of gravity and pressure changes.